Poor sleep and multiple sclerosis: associations with symptoms of multiple sclerosis and quality of life. Issue 11 (27th July 2022) - Laslett, Laura L; Honan, Cynthia; Turner, Jason A; Dagnew, Baye; Campbell, Julie A; Gill, Tiffany K; Appleton, Sarah; Blizzard, Leigh; Taylor, Bruce V; van der Mei, Ingrid
Abstract : Background: Sleep difficulties are common in people with multiple sclerosis (MS), but whether associations between poor sleep quality and quality of life are independent of MS symptoms, obesity and other MS-related factors remains unclear. Methods: Cross-sectional analyses of data from the Australian MS Longitudinal Study (n=1717). Sleep was assessed using the Pittsburgh Sleep Quality Index, Epworth Sleepiness Scale and International Restless Legs Syndrome Study Group Rating Scale; health-related quality of life using the Assessment of Quality-of-Life 8-D. Results: Poor sleep quality was common (67%), and more common than in community samples. Sleep measures clustered independently within MS symptoms. The clusters 'fatigue and cognitive', 'feelings of anxiety and depression', 'pain and sensory', were independently associated with poor sleep quality. Quality-of-Life utility scores were a clinically meaningful 0.19 units lower in those with poor sleep. Sleep quality, daytime sleepiness and restless leg syndrome were associated with reduced quality of life, independent of MS-related symptoms and body mass index. Conclusion: Poor sleep quality is common in MS and was strongly associated with worse health-related quality of life, independent of other MS symptoms and did not cluster with other common MS symptoms. Improving sleep quality may substantially improve quality of life in people with MS.